Privacy in an Age of Cybersurveillance - Weaver, Russell L. (Public Governance, Administration and Finances Law Review, 2024)
This article provides an update en events since Edward Snowden, an employee of a National Security Agency (NSA) contractor, stole and released thousands of classified documents in 2013, revealing that the U.S. government was engaged in a massive secret cybersurveilance operation that was amassing information about people all over the world, including U.S. citizens. In the U.S., Snowden’s revelations sparked a spirited debate regarding privacy rights, and in particular whether the U.S. cybersurveillance operation was appropriate in a democratic system. This article describes the scope of the cybersuveillance program, and examines how the courts and Congress responded to the Snowden revelations, and (in particular) how U.S. society evolved in the following years.